Determinants of Food Safety Practices in Food Handlers: A Literature Review - Suyitno, Suyitno; Suryani, Dyah; Jannah, Arihni Arihatal (Universitas Ibn Khaldun Bogor, 2024)
Food safety is an effort to ensure food is safe for consumption, free from physical, chemical, and biological hazards, so that there is no risk of it causing disease if consumed. Creating these conditions is closely related to food safety practices among food handlers. It is necessary to control food safety practices that can be carried out if the determining factors are known in advance. Thus, this study aims to summarize and describe the determinants of food safety practices among food handlers based on previous research articles. This study uses the literature review method to identify research articles that are relevant to the research objectives. The keywords used are